Correlation between Apolipoprotein E genotype and brain metabolism in amyotrophic lateral sclerosis. (24th October 2018) - Canosa, A.; Pagani, M.; Brunetti, M.; Barberis, M.; Iazzolino, B.; Ilardi, A.; Cammarosano, S.; Manera, U.; Moglia, C.; Calvo, A.; Cistaro, A.; Chiò, A.
Abstract : Background and purpose: The aim of the study was to evaluate the metabolic correlates of Apolipoprotein E ( APOE ) genotype in amyotrophic lateral sclerosis (ALS) and to investigate the role of ε2 as a risk factor for cognitive impairment. Methods: A total of 159 ALS cases underwent APOE and ALS‐related genes analysis, neuropsychological assessment and cerebral 18 F‐2‐fluoro‐2‐deoxy‐D‐glucose positron emission tomography. The APOE genotype was regressed against whole brain metabolism as assessed by 18 F‐2‐fluoro‐2‐deoxy‐D‐glucose positron emission tomography, with age, sex, education, type of onset and C9orf72 status as covariates. Results: Brain metabolism was significantly positively correlated with APOE genotype from ε2/ε2 to ε3/ε4 in the left prefrontal [Brodmann area (BA) 10], orbitofrontal (BAs 11, 45, 47) and anterior cingulate (BA 32) cortices. There was a tendency to a relative hypometabolism going towards the ε2/ε2 extreme. Conclusions: We found a highly significant, relatively lower metabolism in association with the ε2 allele in extra‐motor areas typically affected in frontotemporal dementia (left prefrontal, orbitofrontal and anterior cingulate cortices), strengthening the finding of a role of ε2 as a risk factor for cognitive impairment in ALS. Our data suggested a link between cholesterol homeostasis and neurodegeneration.